Hypoalbuminemia in COVID‐19: assessing the hypothesis for underlying pulmonary capillary leakage. (7th January 2021) - Wu, M. A.; Fossali, T.; Pandolfi, L.; Carsana, L.; Ottolina, D.; Frangipane, V.; Rech, R.; Tosoni, A.; Lopez, G.; Agarossi, A.; Cogliati, C.; Meloni, F.; et al.
Abstract: Background: Since the first observations of patients with COVID‐19, significant hypoalbuminaemia was detected. Its causes have not been investigated yet. Objective: We hypothesized that pulmonary capillary leakage affects the severity of respiratory failure, causing a shift of fluids and proteins through the epithelial–endothelial barrier. Methods: One hundred seventy‐four COVID‐19 patients with respiratory symptoms, 92 admitted to the intermediate medicine ward (IMW) and 82 to the intensive care unit (ICU) at Luigi Sacco Hospital in Milan, were studied. Results: Baseline characteristics at admission were considered. Proteins, interleukin 8 (IL‐8) and interleukin 10 (IL‐10) in bronchoalveolar lavage fluid (BALF) were analysed in 26 ICU patients. In addition, ten autopsy ultrastructural lung studies were performed in patients with COVID‐19 and compared with postmortem findings in a control group (bacterial pneumonia‐ARDS and H1N1‐ARDS). ICU patients had lower serum albumin than IMW patients [20 (18–23) vs 28 (24–33) g L −1, P  < 0.001]. Serum albumin was lower in more compromised groups (lower PaO2 ‐to‐FiO2 ratio and worst chest X‐ray findings) and was associated with 30 days of probability of survival. Protein concentration was correlated with IL‐8 and IL‐10 levels in BALF. Electron microscopy examinations of eight out of ten COVID‐19 lung tissues showed loosening of junctional complexes, quantitatively more pronounced than in controls, and direct viral infection of type 2 pneumocytes and endothelial cells. Conclusion: Hypoalbuminaemia may serve as severity marker of epithelial–endothelial damage in patients with COVID‐19. There are clues that pulmonary capillary leak syndrome plays a key role in the pathogenesis of COVID‐19 and might be a potential therapeutic target. Abstract :